2012
DOI: 10.1007/s12035-011-8230-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Serotonergic Transmission to the Motor and Cognitive Effects of High-Frequency Stimulation of the Subthalamic Nucleus or Levodopa in Parkinson’s Disease

Abstract: Although they are effective at treating the motor impairments that are the core symptoms of Parkinson's disease, current treatments, namely L: -3,4-dihydroxyphenylalanine (L: -DOPA), the gold standard medication and high-frequency stimulation of the subthalamic nucleus (HFS-STN), can lead to cognitive and mood alterations. Many of these side effects, such as depression, anxiety and sleep disturbances, could be related to abnormal functioning of the serotonergic system, but much basic research remains to be don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 169 publications
(164 reference statements)
2
24
0
Order By: Relevance
“…In the present study, however, we cannot rule out an impact of STN‐DBS on the serotonergic system that could participate to the increase in harm avoidance. Indeed, several fundamental studies have shown results consistent with a decrease in serotonergic tonus induced by STN‐DBS . However this serotonergic modulation seems insufficient by itself to explain the increased prevalence of harm avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, we cannot rule out an impact of STN‐DBS on the serotonergic system that could participate to the increase in harm avoidance. Indeed, several fundamental studies have shown results consistent with a decrease in serotonergic tonus induced by STN‐DBS . However this serotonergic modulation seems insufficient by itself to explain the increased prevalence of harm avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in a larger sample of patients, undergoing a prolonged follow-up study, low levels of 5-HT would correlate with specific sub-items related to unconventional aspect of non-motor symptoms well beyond those testable through depression or apathy rating scales, including BDI, HSD or AES. Coping strategies, for instance, are largely impaired in PD patients whereas reduced compliance and lack of adhesion to therapy is largely recognized despite consistent L-dopa-therapy and STN-DBS treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high frequency stimulation (HFS) or lesions of STN has been shown to significantly alleviate oral dyskinesias in rats [79, 94]. STN-HFS in sham-lesioned and DA-lesioned rats has been shown to reduce 5-HT release in several regions, in part via the inhibition of 5-HT neuron activity [95]. Similarly, an action in the output regions of the basal ganglia may be envisioned.…”
Section: Introductionmentioning
confidence: 99%